Can Child-Care Support Policies Halt Decreasing Fertility? - Yasuoka, Masaya (International Journal of Economics and Financial Issues, 2013)
Some earlier papers examine whether child allowances can raise fertility or not in an endogenous fertility model with a defined contribution pension system. They derive that a child allowance can raise fertility. This paper is aimed at deriving the level of child allowances or education subsidies to make the pension system sustainable. A child allowance can raise fertility instantaneously. However, in the long run, fertility might continue decreasing and the pension system might not be sustainable if less child allowance is provided. In a defined benefit system, tax burdens for pension benefits are heavy in an aging society with fewer children. A heavy tax burden reduces the household income and then decreases fertility. Therefore, child allowances must be provided to halt decreasing fertility in the long run. Nevertheless, given parametric conditions, education subsidy of more than a certain level can not halt the decrease of fertility in the long run. Keywords: Child allowances; Education subsidy; Defined benefit; Endogenous fertility JEL Classifications: G23; H55; J13